Is the flipped classroom more effective than the traditional classroom in clinical medical education: a systematic review and meta-analysis - Xu-Ying Shi; Qing Yin; Qiu-Wen Wang; Bing-Rui Lu; Guo-Xiang Li; Shu-Hong Huang; Zhi-Gang Sun (Frontiers in Education)
BackgroundThe flipped classroom teaching method has been increasingly adopted in recent years for teaching clinical medical specialties in medical schools around the world. However, the outcomes of this approach have not been systematically and quantitatively assessed. This meta-analysis aims to rigorously compare the effects of flipped classroom (FC) and traditional classroom (TC) teaching models on students’ learning in clinical medicine.MethodsWe conducted a systematic search for all randomized and quasi-randomized controlled trials (RCTs/Q-RCTs) comparing traditional classrooms and flipped classrooms in the context of clinical medical education. The literature search included the Cochrane Library, PubMed, Embase, and Web of Science, with the final retrieval conducted on October 26, 2024. We screened the literature based on predefined inclusion and exclusion criteria. The quality of each study was assessed using RevMan (Version 5.4). The outcome indicators included theoretical scores, composite scores, skills scores, and student satisfaction. Data extraction and subsequent meta-analysis were performed using Stata 17.0 software.ResultsA total of 12 studies were included in the analysis. The meta-analysis revealed that the flipped classroom (FC) group exhibited significantly higher theoretical scores (SMD = 0.481, 95% CI: 0.214 to 0.748, p = 0.000), composite scores (SMD = 0.642, 95% CI: 0.273 to 1.011, p = 0.001), and skills scores (SMD = 0.660, 95% CI: 0.312 to 1.008, p = 0.000) compared to the traditional classroom (TC) group. However, no statistically significant difference was observed in student satisfaction (SMD = −0.195, 95% CI: −1.081 to 0.691, p = 0.667).ConclusionThe flipped classroom teaching method is more effective in enhancing the theoretical scores, composite scores, and skill scores of clinical medicine students compared to the traditional classroom teaching method. However, there was no statistically significant difference in student satisfaction between the two teaching approaches. Due to the limitations of the included studies, further robust randomized controlled trials (RCTs) across diverse educational contexts are necessary to validate these findings.